DYBBUK OR THE JEWISH (NON)PRESENCE IN UMAN - Molisak, Alina (Porównania, 2019)
Alina Molisak, DYBBUK OR THE JEWISH (NON)PRESENCE IN UMAN. “PORÓWNANIA” 1 (24), 2019. Vol. XXIV, P. 111-121. ISSN 1733-165X. In this article, I describe the functioning of memory and Jewish (non)presence within the space of contemporary Humań. In my analysis, I focus on both Krzysztof Kopczyński’s film “Dybbuk. A Tale of Wandering Souls” and the book by Kopczyński and Sajewich entitled “Dybbuk. A story about the world’s insignificance”. While at it, I analyze different formulas of memory and various kinds of identity articulations by both chasidic Jews as well as Ukrainians.